Experimental and Theoretical Trends of PGM-Free Electrocatalysts for the Oxygen Reduction Reaction with Different Transition Metals. Issue 7 (1st January 2019) - Martinez, Ulises; Holby, Edward F.; Babu, Siddharth Komini; Artyushkova, Kateryna; Lin, Ling; Choudhury, Samrat; Purdy, Geraldine M.; Zelenay, Piotr
Abstract : Replacement of platinum-based electrocatalysts to facilitate the oxygen reduction reaction (ORR) in proton exchange fuel cells remains an outstanding challenge. Significant progress in the development of platinum group metal-free (PGM-free) electrocatalysts has been reported but a fundamental understanding of how these materials catalyze the ORR remains elusive. In this work, we report our efforts to synthesize and characterize PGM-free electrocatalysts with different transition metals (M = Fe, Co, and Mn) in order to better understand the most plausible active site structures and ORR reaction pathways. Our findings indicate that PGM-free electrocatalysts synthesized via a dual nitrogen precursor, polyaniline and cyanamide, synthesis process but with varied transition metal precursors resulted in the following ORR activity trend: Fe > Co > Mn. Furthermore, similar densities of active sites across the three synthesized materials were calculated using an established molecular probe technique. The relative experimental activities are consistent with trends determined via density functional theory (DFT) modeling that suggests spontaneous OH ligand modification of active sites.